Perancangan User Experience Aplikasi Pusat Kebugaran dengan Pendekatan Human-Centered Design (Studi Kasus Kota Malang) - Muhammad Fachri Pratama; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Fitness center information is currently difficult to know because many potential users have to conduct a direct survey of fitness center information. The results of an interview with one of the informants, namely the data listed, are not by the user's wishes, such as the cost of exercising, contacts, and how to become a fitness center member. The design is carried out using the Human-Centered Design method, which aims to make a valuable system to meet user needs, Effectiveness, Efficiency, and user satisfaction. Testing is done using Usability Testing and UEQ. The results of this study are expected to make it easier for potential users to find detailed information from the fitness center. The Usability Testing results used to get results, Effectiveness is 97% for users and 100% for managers, Efficiency is 0.176 goals/sec for users, and 0.106 goals/sec for managers. The results of the calculation of the satisfaction aspect using SUS get an average value of 77.59, including a suitable category for users, and 70, including ok type for managers. UEQ calculations get benchmark results for users, namely Attractiveness (2.04 Excellent), Perspicuity (2.01 Excellent), Efficiency (1.91 Excellent), Dependability (1.88 Excellent), Stimulation (1.88 Excellent), and Novelty (1.60 Good). In addition, the manager's results are Attractiveness (2.28 Excellent), Perspicuity (2.00 Good), Efficiency (2.17 Excellent), Dependability (2.25 Excellent), Stimulation (2.25 Excellent), and Novelty (1.33 Good).